PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN INTELLECTUAL CAPITAL: PADA PERUSAHAAN IC INTENSIVE - Arifah, Dista Amalia (Jurnal Akuntansi dan Keuangan Indonesia, 2012)
Intangible asset proxied by Intellectual Capital has important role to drive companies values creation. Although many companies have applied corporate governance mechanism in order to have IC disclosure recognition, most of them do not focus on Intellectual Capital disclosure yet. The aim of this study is to analyze the influence of corporate governance mechanisms consisting of size of the board commissioners, the independence level of independent commissioner, the activities of independent commissioners, and audit committee on the intellectual capital disclosures of the companies listed in BEI in 2009 using intensive ICs category with the adding of kontrol variables. This study will provide an illustration on how the mechanisms of corporate governance practices and IC disclosure become a value creation source for the company. There are a total of 176 companies categorized as IC intensive. Using a purposive sampling method, 45 companies were selected as samples. The 2009 annual reports of the companies are used as secondary data source of this research. Furthermore, to get ICs disclosure data content analysis technique was used both for quantity and quality terms. The results indicate that audit committee is the only corporate governance mechanism that significantly affects the level of IC disclosures.